2009
DOI: 10.1007/s00775-009-0486-8
|View full text |Cite
|
Sign up to set email alerts
|

DNA binding and oxidative DNA damage induced by a quercetin copper(II) complex: potential mechanism of its antitumor properties

Abstract: The interaction of a quercetin copper(II) complex with DNA was investigated using UV-vis spectra, fluorescence measurement, viscosity measurement, agarose gel electrophoresis, and thiobarbituric acid reactive substances assay. The results indicate that the quercetin copper(II) complex can promote the cleavage of plasmid DNA, producing single and double DNA strand breaks, and intercalate into the stacked base pairs of DNA. Moreover, the complex can induce oxidative DNA damage involving generation of reactive ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
85
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(90 citation statements)
references
References 33 publications
4
85
0
1
Order By: Relevance
“…In other study, the same authors showed that quercetin-copper(II) complex promoted the cleavage of plasmid DNA, producing single and double DNA strand breaks, and intercalated into the stacked base pairs of DNA. Moreover, the complex showed pro-oxidative properties and induced oxidative DNA damage involving generation of reactive oxygen species such (H 2 O 2 and CuOOH) [12]. Other study of Tan et al showed that antitumor activity of quercetin zinc(II) complex might be related to its intercalation into DNA [13].…”
Section: Introductionmentioning
confidence: 98%
“…In other study, the same authors showed that quercetin-copper(II) complex promoted the cleavage of plasmid DNA, producing single and double DNA strand breaks, and intercalated into the stacked base pairs of DNA. Moreover, the complex showed pro-oxidative properties and induced oxidative DNA damage involving generation of reactive oxygen species such (H 2 O 2 and CuOOH) [12]. Other study of Tan et al showed that antitumor activity of quercetin zinc(II) complex might be related to its intercalation into DNA [13].…”
Section: Introductionmentioning
confidence: 98%
“…As of today, very few copper complexes have been described that induce apoptosis through the involvement of the Caspase 3 (C3) [16][17]. The mechanism of C3 activation in copper-mediated cell death has not been fully elucidated [18].…”
Section: Introductionmentioning
confidence: 99%
“…Copper has been shown to influence the bioactivity or production of a number of angiogenic factors including VEGF-A [5,8] and shares some of the pathways utilized by hypoxia to regulate VEGF-A expression [2,5] demonstrated that copper is having anti-tumor activity [9]. Copper is also required in hemoglobin synthesis and in the catalysis of metabolic oxidation [10].…”
Section: Discussionmentioning
confidence: 99%